At skrive queer historie - Nyegaard, Niels (Slagmark - Tidsskrift for idéhistorie, 2021)
The article examines how queer theory has affected research on Danish gender and sexuality history from the year 2000 and up until today. The article does so by pursuing two analytical objectives. First, the article identifies a series of significant elements within queer theory as a theoretical framework. The article categorises the elements as: 1) an anti-essentialist point of departure, 2) a critical view on the normal, and 3) an opposition against proper objects. Second, the article examines how researchers with an interest in Danish gender and sexuality history have deployed these elements in their own studies in recent decades. The article makes a broad examination of historical research in academia and includes studies from disciplines like history, literary scholarship, sociology, and gender studies. Its argument is that queer theory has affected research on Danish gender and sexuality history by building on existing historical studies of homosexuality and by taking these studies in new directions.